Answer:
c1) adjacent
c2) not adjacent
c3) adjacent
c4) not adjacent
c5) adjacent
c6) not adjacent
d1) 20°
Complement: 90° - 20° = 80°
Supplement: 180° - 20° = 160°
d2) 77°
Complement: 90° - 77° = 13°
Supplement: 180° - 77° = 103°
d3) 101°
Complement: doesn't have a complement.
Supplement: 180° - 101° = 79°
d4) 90°
Complement: 90° - 90° = 0°
Supplement: 180° - 90° = 90°
d5) 96°
Complement: doesn't have a complement
Supplement: 180° - 96° = 84°
d6) x
Complement: 90° - x
Supplement: 180° - x
d7) y
Complement: 90° - y
Supplement: 180° - y
Answer:
B
Step-by-step explanation:
Transformation that maps triangle XYZ into triangle X'Y'Z' is a translation 3 units to the right and 1 unit down, because
- X(0,0)→X'(3,-1);
- Y(2,3)→Y'(5,2);
- Z(4,-1)→Z'(7,-2).
So, the algebraic ru;e of the transformation is
(x,y)→(x+3,y-1)
Answer:
f(x) = 2(x+4)(x+4)(x+4)(x-10)
Step-by-step explanation:
Here, we want to write a polynomial function with leading coefficient of 2, root - 4 with multiplicity 3 ( meaning it appears 3 times);
and root 10 with multiplicity 1
If x = -4
Then in linear form, we have x + 4
if x = 10, in linear form, we have x -10
So the polynomial is;
f(x) = 2(x+4)(x+4)(x+4)(x-10)